Association of SHMT1 gene polymorphisms with the risk of childhood acute lymphoblastic leukemia in a sample of Iranian population - Bahari, G; Hashemi, M; Naderi, M; Sadeghi-Bojd, S; Taheri, M (Cellular and Molecular Biology, 2016)
The enzymes serine hydroxymethyltransferase 1 (SHMT1) regulate key reaction in folate-mediated one-carbon metabolism. In the current study we aimed to examine the possible association between SHMT1 gene polymorphisms and childhood acute lymphoblastic leukemia (ALL) in a sample of Iranian population. The rs9901160, rs2273027, rs9909104, rs1979277, and rs11868708 gene polymorphisms of SHMT1 were genotyped in 120 children diagnosed with ALL and 120 healthy children by the polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP). The results showed that rs9901160, rs2273027 as well as rs1979277 polymorphism significantly increased the risk of childhood ALL (P0.05). In conclusion, our results suggest that the polymorphisms of SHMT1 gene are associated with childhood ALL risk in a sample of Iranian population. Further studies with larger sample sizes and different ethnicities are necessary to verify our findings.